Computer simulation risks - Bonem, Joe M. (Knovel, 2012)
"Computer simulation in chemical engineer[ing] provides a quick and often highly accurate method of doing calculations for many different kinds of unit operations. Like many other things with a positive attribute, these computer simulations also have negative risks. The capability of the computers to quickly do simulations has often led to a failure of the user to understand the basic engineering aspects. Typical risks associated with this user failure are discussed."--Knovel